Analysis of balanced scorecard-based servqual criteria based on hesitant decision-making approaches - Dinçer, Hasan; Yüksel, Serhat; Martinez, Luis (Pergamon-Elsevier Science Ltd, 2019)
The measurement of quality of services has an important influence in the companies' competence, being even more relevant in the banking sector because of the high competition to keep and attract customers. Due to this fact, this paper proposes a balanced scorecard based SERVQUAL to rank competitors in the banking sector. The analysis will deal with hesitant fuzzy information that models the hesitancy of the experts involved. This analysis will be applied for weighting criteria and dimensions, ranking alternatives and different results that will define the Turkish banking sector. Its main goal is to show that banks should be more willing to help and support their customers to increase the quality of their services. Therefor the analysis aims at showing which is the most relevant factor in the balanced scorecard based-SERVQUAL dimensions according to the correlation coefficient? It also aims at providing a clear view about what type of actions should take banks to be closer to the customers. Additionally, it will be identified which is the importance of the different dimensions of the approach? Eventually the main conclusions obtained from the analysis will be detailed regarding the quality services offered by banks in Turkey and different recommendations will be elicited to increase the banks performance in service quality according to the criteria and dimensions emphasized in this study.
WOS: 000468710600001
Keywords: Multi-Criteria Decision Making; Servqual; Hesitant Fuzzy Sets; Dematel; Vikor